Fantasy Parody in the Design of the Advertisement (Al-Academy, 2021)
This research deals with the topic (Fantasy Parody in the Design of the Advertisement) in view of the important role that fantasia plays in designing the most creative and attractive advertisements to the recipients. The research problem lies in accordance with the following question:What is the Fantasy Parody in the Design of the Advertisement?It means the imagination, the unfamiliar; and features that emerge for it that distinguish it from other concepts. Fantasy advertisement is creativity in innovative ways, either through collage, merging, or the use of various artistic expressions in terms of intellectual and cultural awareness. When uses in the parody of advertisement, it has helped to come up with an aesthetic experience with new technical values and standards that are incredible in order to bring about changes and denunciation of what was done in the original image; as it revives aesthetic values within. The research also takes account of the goal of unveiling fantasy parodies in the advertisement design. The boundaries of the temporal study have been represented by the period (2017 - 2020) as being a period that represents the latest design developments and the broadest time range experienced by the designer. Models have been chosen from America according to the place limit, taking it ast he leading of the largest advertisement institutions. The Second Chapter tackles the (Theoretical Framework): The First Section deals with (Graphic Fantasy); while the Second Section discusses the (Parody of Design Composition), as for the Third Section, it involves with the (Employment of Fantasy Parody in the Design of the Advertisement). The researcher has dealt with the research procedures which include the research methodology and society, which are the designs of fantasy advertisements, while the research sample have been chosen according to the requirements of the nature of the research. The utilitarian and communicative function has been achieved by attracting attention, as designs have helped in models (1) (2) (3) in terms of making the advertisement material likable .The most important findings are: The form is associated with the content within the work design represented by the fantasy advertisement, through the aesthetic, intellectual and intellectual and communication values that the designer instills in the recipient. The research concludes with recommendations and proposals